New application of non-binary Galois fields Fourier transform: digital analog of convolution theorem - Elizaveta S. Vitulyova; Dinara K. Matrassulova; Ibragim E. Suleimenov (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
It is shown that the use of the representation of digital signals varying in the restricted amplitude range through elements of Galois fields and the Galois field Fourier transform makes it possible to obtain an analogue of the convolution theorem. It is shown that the theorem makes it possible to analyze digital linear systems in same way that is used to analyze linear systems described by functions that take real or complex values (analog signals). In particular, it is possibile to construct a digital analogue of the transfer function for any linear system that has the property of invariance with respect to the time shift. It is shown that the result obtained has a fairly wide application, in particular, it is of interest for systems in which signal processing methods are combined with the use of neural networks.